Bipolarized intrinsic faradaic layer on a semiconductor surface under illumination. Issue 4 (4th November 2022) - Xue, Mengfan; Chu, Zhiqiang; Jiang, Dongjian; Dong, Hongzheng; Wang, Pin; Sun, Gengzhi; Yao, Yingfang; Luo, Wenjun; Zou, Zhigang
Abstract: Interface charge transfer plays a key role in the performance of semiconductors for different kinds of solar energy utilization, such as photocatalysis, photoelectrocatalysis, photochromism and photo-induced superhydrophilicity. In previous studies, different mechanisms have been used to understand interface charge transfer processes. However, the charge transfer mechanism at the solid/liquid interface remains a controversial topic. Here, taking TiO2 as a model, we find and prove, via experiments, the new characteristic of photo-induced bipolarity of the surface layer (reduction faradaic layer and oxidation faradaic layer) on a semiconductor for the first time. Different from energy level positions in the classic surface states transfer mechanism, the potential window of a surface faradaic layer is located out of the forbidden band. Moreover, we find that the reduction faradaic layer and oxidation faradaic layer serve as electron and hole transfer mediators in photocatalysis, while the bipolarity or mono-polarity of the surface layer on a semiconductor depends on the applied potential in photoelectrocatalysis. The new characteristic of bipolarity can also offer new insights into the charge transfer process at the semiconductor/liquid interface for solar energy utilization. Abstract : Luo et al. find the photo-induced bipolarity characteristic of a faradaic layer on semiconductor surface and also propose electrochemical potential as a simplified descriptor for the faradaic layer.